Optimalisasi Media Sosial untuk Pemasaran Produk UMKM di Desa Mekarmukti - Etty Zuliawati Zed; Muhammad Mufidz Aiman; Afrizal Erlangga Fathir Maulana; Muhammad Candra (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Small and Medium Enterprises (SMEs) play a crucial role in economic growth but often face challenges in expanding their market reach. Utilizing social media as a marketing platform can be an effective and efficient solution to enhance the competitiveness of SMEs. This community service activity aims to optimize the use of social media for product marketing by SMEs in Mekarmukti Village through intensive training. The training covers an introduction to social media platforms, techniques for creating engaging content, digital marketing strategies, and performance analysis. The methods employed include participatory approaches, hands-on practice sessions, and group discussions. The results of the activity indicate an increase in participants' understanding and skills in using social media to promote products. Furthermore, participants are capable of creating creative content and designing more structured marketing strategies. Consequently, this training has a positive impact on the development of SME marketing in Mekarmukti Village and is expected to increase income and business sustainability for SME entrepreneurs..